You are on page 1of 5

# Bernoullis Equation

## If the equation can be translated into the form:

dy
+ P ( x ) y=Q ( x ) y n
dx
A substitution can be made so that it conforms to the form:

dy
+ P ( x ) y=Q ( x ) y
dx
And hence can be solved using the methods developed in the proceeding topic such
equations are called Bernoullis Equation.
Take note that if n=0, 1st equation equal to the 2nd equation, therefore the foregoing
techniques applies only to the case when n 0
we first multiply the equation

( 1n ) y n

By putting

(1n) y

dy
n
+ ( 1n ) P ( x ) y =( 1n ) Q(x)
dx
z= y 1n

and hence

dz=( 1n ) yn ,

dz
+ ( 1n ) P ( x ) z=( 1n ) Q( x)
dx
And notice that equation is now linear in z, the method presented for solving linear
equation of order one can now be applied.

## EXAMPLE: solve the equations

1)

y ( 6 y 2x1 ) dx +2 xdy =0

## ( 6 y 2xy y ) dx+ 2 xdy=0

3

6y
y 2 dy
+ =0
2 x 2 2 x dx

n=3

2 y3 dy
1
6
+ 1+ y2=
dx
x
x

( )

1
6
P ( x )=1+ Q ( x ) =
x
x

z= y dz=2 y
( 1+ 1x ) dx

2)

z=( x e x ) ( x e x )

z=x1 ex ( 6 e x ) dx +C x1 ex
xz=6+C e

=e

=e

y=1 Q ( x ) dx +C 1

3 2 x

dyPydx=Q y n dx

( )

dz
1
6
+ 1+ z= linear z
dx
x
x

( )

x+lnx

=e x elnx

( 6x ) dx+ C ( x e )

x 1

z= y2

=x e x

[ z=6 x1+C x1 ex ] x

2 x

x=6 y +C y e

dy
y =x y 3 e2 x dx
dx
n=3

dy 1
1
3 y 3 (
1+ y=
2 y 3 )
dx 2
x
x

z=6 x1 ex ( e x ) +C x 1 ex

[ x y 2=6 +C ex ] y 2

y = yx y e

( 13 ) y3

2
2 xdx

3 2 x

dy ydx =x y e

P ( x )=1 Q ( x )=x e2 x

dx
2 dx
=e

e2 x 2
=x +C
y2

e 2 x y 2=2 xdx +C

3)

dy
= y+ y 3
dx
z=

4)

dy
y= y 3
dx

(e2 x +C )
e

n=2

1
P ( x )= Q ( x ) =x
x

5)

x 3
+C
3

dy y
+ = y2
dx x
P ( x )=

n=3

e 2 x = y 2 ( x2 +C )

dz
+2 z=2
dx

z= y2

=e

2dx

=e2 x

y2=C e2 x +1

2x

dy 1
2
y=xy
dx x

xz=

y2 ( e2 x ) =2 (x e2 x ) ( e 2 x ) dx +C

z=( 1n ) Qdx+C

=e2 x

z= y dz= y
1x dx

=e

=x

x x3
=
+C
y
3

n=2

1
Q ( x ) =1
x

1
=x (lnx+C)
y

1 dy 1 1
y =x
y 2 dx x

xdz
+ z=x2
dx

dz 1
+ z =x
dx x

xz= x2 dx

1 x2 C
=
+
y
3
x

z= y1

=e

1 dy 1 1
+ y =1
2
y dx 1 x
1
dx
x

lnx

=e

dz 1
z=1
dx x
1
x

1
dx
z=
x
x

z
=lnx+C
x

6)

dy 1
+ y =e x y 4
dx 3

n=4

dz
z =3 e x
dx

dy
+ y=x y 3
dx

n=3

dz 2
z=2
dx x

1 dz 2
x
3 z= 2 cosx
2
dx
x
x
x
9)

dy
+ y= y 2 x2 lnx
dx

dz 1
+ z=xln x
dx x
1 dz 1
z=ln x
x dx x 2
1
=x ( 1lnx ) +C
xy

2
Q ( x ) =2
x

n=2

dx
2
x

e z= 3 dx
x

1
z= cosxdx
x2

1 dy 2 1
2
+ y =x cosx
2
y dx x

dx
2
x

x y

z= y dz= y

=sinx+ C

=e2 lnx=e ln x

dx
1
x

=e1 lnx==

1
x2

1
=x 2 (sinx+C)
y

1 dy 1 1
+ y =xln x
y 2 dx x

=e

1
z= lnx dx +C
x

1
2
x

1
2 x +C x 2

=e
1

=e

y 2=

1 dz 1
+ z=1
2 dx x

=e2 lnx=e ln x

z= y1 dz= y2

dz 1
z=xln x
dx x

=ex

1 dy 1 2
+ y =1
3
y dx x

dz 2
2
z=x cosx
dx x

n=2

1 dz 1
+ z =e x
3 dx 3

1
x
=e (3 x +C)
3
y

z=2 x+C x 2

dy 2
+ y=x 2 cosx y 2
dx x
dz 2
2
+ z=x cosx
dx x

1
=3 x +C
y3
z= y2 dz=2 y 3

P ( x )=

1
1
z=(2 ) (1 ) + C
2
x
x

8)

xdx
=e

P ( x )=1 Q ( x )=3 e x

ex z=3 x+C
7)

1 dy 1 3 x
+ y =e
4
y dx 3

z= y3

1
x

1
1
z= xlnx x dx +C
x
x

dy
= ycotx+ y 3 cscx
dx

10)

1 dy
cotx y2=cscx
3
dx
y
P ( x )=cotx Q ( x )=2 cscx
sin 2 x
sin

x
2

2
y =

dy
cotxy=cscx y 3
dx

1 dz
cotxz=cscx
2 dx
2

=e

dz
+2 sinxcosxz =2 sinx
dx

cosx
dx
sinx

=e 2 ln ( sinx )

n=3

z= y2 dz=2 y 3

dz
+2 cotxz=2 cscx
dx
=sin 2 x

zsi n x= (2 ) (cosx )+ C

sin 2

x
=2 cosx+C
y2